2020
DOI: 10.1021/acs.inorgchem.9b03364
|View full text |Cite
|
Sign up to set email alerts
|

Two Highly Water-Stable Imidazole-Based Ln-MOFs for Sensing Fe3+,Cr2O72–/CrO42– in a Water Environment

Abstract: Developing highly stable materials for harmful ion detection in a water environment is of much importance and challenging. Here, two three-dimensional porous structures (termed as Eu-MOF and Tb-MOF) were successfully constructed by the strategy of anchoring Eu3+/Tb3+ and rigid 1,2,4,5-benzenetetracarboxylic acid (H4BTEC) imidazole units (H3ICA) onto its frameworks. The obtained Eu-MOF and Tb-MOF display high water stability and fluorescence stability up to 30 days. Furthermore, luminescent studies reveal that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 182 publications
(71 citation statements)
references
References 43 publications
1
70
0
Order By: Relevance
“…Either too few or excessive intake of Fe 3+ could result in different kinds of disorders as well as severe diseases like Parkinson's disease and inflammation [106]. Yu et al [107] constructed stable MOFs-based sensors (Eu-MOF and Tb-MOF) for Fe 3+ by selecting rigid organic ligands of MOFs. Eu-MOF and Tb-MOF displayed strong water stability, heat resistance and luminescence stability at a wide PH range.…”
Section: Cationsmentioning
confidence: 99%
“…Either too few or excessive intake of Fe 3+ could result in different kinds of disorders as well as severe diseases like Parkinson's disease and inflammation [106]. Yu et al [107] constructed stable MOFs-based sensors (Eu-MOF and Tb-MOF) for Fe 3+ by selecting rigid organic ligands of MOFs. Eu-MOF and Tb-MOF displayed strong water stability, heat resistance and luminescence stability at a wide PH range.…”
Section: Cationsmentioning
confidence: 99%
“…These channels of MOFs were filled with cations and exhibited selective adsorption and recyclable detection of Cr 3+ in aqueous solutions; it all boiled down to the structure and chemical bond of the fluorescent MOFs [136]. Yu et al [137] reported two imidazole-based Ln-MOFs for Cr 2 O 7 2or CrO 4 2detection in water, these MOFs had high fluorescence stability in water more than 30 days.…”
Section: Heavy Metal Detectionmentioning
confidence: 99%
“…Rare earth ion complexes are widely used as the probe molecules because of the good fluorescent properties. [3,4] The luminescence of rare earth metals are mainly ascribed to the f-f transition within 4 f electron orbits, whereas the electric-dipole f-f transition of rare earth ion is inherent forbidden. Even though some magnetic-dipole f-f transition of rare earth metal ions are allowed, their intensity is too poor to carry out in actual applications.…”
Section: Introductionmentioning
confidence: 99%